2010
DOI: 10.1590/s0066-782x2010005000014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores de risco para hipertensão em uma população urbana brasileira

Abstract: Background: The available studies have not fully analyzed the several factors involved in the genesis of hypertension (HT), especially the association among blood pressure, urinary sodium excretion and renal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
1
43

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 31 publications
6
24
1
43
Order By: Relevance
“…Both types of obesity were associated with AH (p < 0.001), and this kind of finding was observed in other states of the federation 5,36,37 . However, abdominal obesity has been pointed out as being more harmful to health then overall obesity.…”
Section: Discussionsupporting
confidence: 65%
“…Both types of obesity were associated with AH (p < 0.001), and this kind of finding was observed in other states of the federation 5,36,37 . However, abdominal obesity has been pointed out as being more harmful to health then overall obesity.…”
Section: Discussionsupporting
confidence: 65%
“…Other studies have also shown no differences in these variables, even between the normotense and hypertense groups. [28][29][30][31][32] Knowing that alterations provoked in the blood vessels by DM and deslipidemia gradually settled down, associated to the fact that there is no available information concerning the time of diagnosis of these risk factors in each of the individuals, it is possible to justify the lack of association in our results. Sharabi et al 21 found no difference in blood glucose levels, total cholesterol and triglyceride levels between the normoreactive and the hyperreactive groups.…”
Section: Discussionmentioning
confidence: 99%
“…These factors can be divided in two categories: the changeable ones (environmental and behavior), such as smoking, high serum cholesterol, systemic arterial hypertension, physical inactivity, diabetes, obesity and stress; and the unchangeable ones (genetic and biological), for example: heredity, sex and age 2,3 . Studies have shown high prevalence of individuals with at least one RF 2,4 , which highlights the multifactorial origin of the CVD and reinforces the need of implementation of actions which aim at health promotion, as well as prevention of these diseases 3,5 . Among the RF, we can mention sedentarism, which, in Brazil, according to the Brazilian Institute of Geography and Statistics, affects about 80.8% of the adults and its association with other RF may lead to the development of CVD 6 .…”
Section: Introductionmentioning
confidence: 92%
“…Individuals who self-declared have been smokers for over one year and daily ingested alcohol were considered positive for these factors. Diabetes mellitus, total cholesterol and triglycerides were considered present when the subjects had medical diagnosis of such factors and/or made use of medication specific to these conditions 2,4,5 . In order to assess the presence of stress, the inventory of stress symptoms by Lipp (ISSL) was used 14 .…”
Section: Risk Factors Analyzedmentioning
confidence: 99%